"Good" and "acceptable" English in L2 research writing: Ideals and realities in history and computer science. Issue 30 (November 2017) - Hynninen, Niina; Kuteeva, Maria
Abstract: In light of the recent developments on the international publishing scene, increasingly dominated by L2 writers of English, the question of what is considered to be "good" and "acceptable" English calls for further research. This paper examines in what ways researchers describe the English used for research writing in their field. Interview data were collected from historians and computer scientists working in Finland and Sweden. Our analysis points towards some differences in the way researchers perceive "good" writing in English in their field, and what they themselves report to practice as (co-)authors, readers/reviewers, and proofreaders. The discrepancy between the ideals and realities of research writing in English was clear in the case of the historians. Our findings suggest that in research writing for publication, there is a pull towards some form of standard norm. This standard can be jointly negotiated during the writing, reviewing, and proofreading process. It may also develop in different directions in different disciplines, but it is likely to be based on the principles of understandability and clarity. Highlights: Researchers' descriptions of English in their field vary between disciplines. Historians admire elegance but strive for understandability. Computer scientists value clarity and correctness. There seems to be a pull towards some form of standard language in research writing. Writing for publication in English requires adjustment from L1 and L2 writers alike.